The likely effects of thermal climate change on vertebrate skeletal muscle mechanics with possible consequences for animal movement and behaviour. Issue 1 (31st October 2019) - James, Rob S; Tallis, Jason
Abstract : Changes in temperature, caused by climate change, can alter the amount of power an animal's muscle produces, which could in turn affect that animal's ability to catch prey or escape predators. Some animals may cope with such changes, but other species could undergo local extinction as a result. Abstract: Climate change can involve alteration in the local temperature that an animal is exposed to, which in turn may affect skeletal muscle temperature. The underlying effects of temperature on the mechanical performance of skeletal muscle can affect organismal performance in key activities, such as locomotion and fitness-related behaviours, including prey capture and predator avoidance. The contractile performance of skeletal muscle is optimized within a specific thermal range. An increased muscle temperature can initially cause substantial improvements in force production, faster rates of force generation, relaxation, shortening, and production of power output. However, if muscle temperature becomes too high, then maximal force production and power output can decrease. Any deleterious effects of temperature change on muscle mechanics could be exacerbated by other climatic changes, such as drought, altered water, or airflow regimes that affect the environment the animal needs to move through. Many species will change their location on a daily, or even seasonal basis, to modulate the temperature that they are exposed to, thereby improving the mechanical performance of their muscle. Some species undergo seasonal acclimation to optimize muscle mechanics to longer-term changes in temperature or undergo dormancy to avoid extreme climatic conditions. As local climate alters, species either cope with the change, adapt, avoid extreme climate, move, or undergo localized extinction events. Given that such outcomes will be determined by organismal performance within the thermal environment, the effects of climate change on muscle mechanics could have a major impact on the ability of a population to survive in a particular location.